Colonialism and modern social theory - Bhambra, Gurminder K.; Holmwood, John (Cambridge Polity Press, 2021)
Modern society emerged in the context of European colonialism and empire. So, too, did a distinctively modern social theory, laying the basis for most social theorising ever since. Yet colonialism and empire are absent from the conceptual understandings of modern society, which are organised instead around ideas of nation state and capitalist economy.
Keywords: Colonialism; Social theory; Sociology